Mycobacterium shimoidei cavitary pneumonia: A rare case report, literature review - Siddartha Guru; David Ingram (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Mycobacterium shimoidei is a rare non-tuberculous mycobacterium (NTM) which causes pneumonia. Since its discovery in 1975, less than 50 cases have been published and this would be only the fourth case in the US. We present a case of Mycobacterium shimoidei in a 72-year-old male with symptoms of cough, dyspnea, and weight loss with cavitary lung lesion on imaging. Sputum cultures grew Mycobacterium shimoidei in two separate collections, and the patient was treated with oral azithromycin, ethambutol, and rifabutin empirically. Though due to medication side effects rifabutin was stopped and other antibiotics were attempted based on susceptibilities but he was unable to tolerate any of them. Thus, only a two-drug regimen including ethambutol and azithromycin was used, on which he improved clinically and cavitary lung lesions decreased in size. In addition, we did a literature review and compiled 41 previously published cases of Mycobacterium shimoidei.